STRATEGI KOMUNIKASI DALAM MENANGGULANGI PENYEBARAN BERITA HOAKS DI MEDIA SOSIAL (Studi Kasus Diskominfosantik Kalimantan Tengah) - Siti Johara; Desi Erawati; Heri Setiawan (Communicative : Jurnal Dakwah dan Komunikasi, 2023)
The world is currently experiencing a significant cultural shift and is having an impact on advances in technology and information, including social media which is the main tool for spreading hoax information. The aim of this research is to determine Central Kalimantan Diskominfosantik's strategy in dealing with the spread of hoax news on social media. Using qualitative descriptive research methods and David K. Berlo's SMCR communication theory model: source, message, media channels and recipients. Based on research results, communication strategies in dealing with hoax news on social media are quite effective. Look for sources and collect information first from relevant agencies or institutions. Messages written in the news will immediately be asked whether someone has made a statement or not, that's the filter. After receiving verification or validation that the news is fact or a hoax, the news will be released with a hoax label on official news sites and social media channels. Communication strategies to increase public awareness include appeals, media literacy education seminars, outreach to all stakeholders.